DAYA REPELAN KOMBINASI MINYAK ATSIRI JERUK NIPIS ( Citrus aurantifolia Swingle) DAN MINYAK SERAI (Andropogon nardus L) DALAM SEDIAAN GEL DENGAN FORMULA CMC DAN GLISERIN TERHADAP GIGITAN NYAMUK Aedes aegypti - , LENDATU KRISTIANA, Dra. Tri Murini, Apt, M.Si ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Dengue Hemorrhagic Fever is an infectious disease. There are 2 kind of repellents, synthetic repellent and botanical. Botanical repellent has a lower rejection times but, have a little more adverse effect than synthetical repellent. Combination essential oil of limeâs and citronella oil which is the active ingredient botanical repellents expected to increase time of rejection. Objective: To determine the power of repellents and find the best concentration of combination essential oil of limeâs and citronella oil. Method: This research was a true experimental study using Fraddin and Day 2002 guidance. Result: The best average of rejection time is combination essential oil of limeâs 7,5% and citronella oil 2,5% with the time of rejection is 1490 seconds. Conclusion: The combination of repellent essential oil of limeâs and citronella in the form gels with CMC and glycerin formula have a power as a repellent againts Aedes aegypti mosquito bites.